2019
DOI: 10.1089/dia.2019.0157
|View full text |Cite
|
Sign up to set email alerts
|

Sotagliflozin Added to Optimized Insulin Therapy Leads to Lower Rates of Clinically Relevant Hypoglycemic Events at Any HbA1c at 52 Weeks in Adults with Type 1 Diabetes

Abstract: Background: Hypoglycemia rates usually increase when insulin treatment is intensified to improve glycemic control. We evaluated (post hoc) hypoglycemic rates in adult patients with type 1 diabetes (T1D) on sotagliflozin (a dual sodium-glucose cotransporter [SGLT] 1 and 2 inhibitor) in two phase 3, 52-week clinical trials (inTandem 1 and 2; NCT02384941 and NCT02421510). Materials and Methods: We analyzed rates of documented hypoglycemia (level 1, blood glucose ‡54 to <70 mg/dL) and clinically important hypoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…In clinical trials, patients with type 1 diabetes who received sotagliflozin 200 or 400 mg added to insulin experienced significant improvements in glycemic control (including A1C, 2-h postprandial glucose, and time in range), and improved body weight, blood pressure, and patient-reported outcomes. Patients receiving sotagliflozin also had a significant reduction in the number of hypoglycemic (blood glucose ≤55 mg/dL) and severe hypoglycemic events (400-mg group only) ( 12 , 13 , 28 , 29 ). In these trials, the AE profile was generally consistent with that observed with SGLT2 inhibitors in type 2 diabetes trials, including an increased incidence of genital mycotic infections and DKA.…”
Section: Discussionmentioning
confidence: 96%
“…In clinical trials, patients with type 1 diabetes who received sotagliflozin 200 or 400 mg added to insulin experienced significant improvements in glycemic control (including A1C, 2-h postprandial glucose, and time in range), and improved body weight, blood pressure, and patient-reported outcomes. Patients receiving sotagliflozin also had a significant reduction in the number of hypoglycemic (blood glucose ≤55 mg/dL) and severe hypoglycemic events (400-mg group only) ( 12 , 13 , 28 , 29 ). In these trials, the AE profile was generally consistent with that observed with SGLT2 inhibitors in type 2 diabetes trials, including an increased incidence of genital mycotic infections and DKA.…”
Section: Discussionmentioning
confidence: 96%
“…Vigersky also proposed a scoring system based on the combination of HbA1c with the risk of hypoglycemia (also using incidence of SH requiring assistance from others). 23,49 With the current widespread availability of CGM and the ability to measure %TBR using any desired threshold (including, but not limited to <54, 63, or <70 mg/dL), it is likely that the metric %TBR would usually be preferable to use of incidence of SH, 1,23,[41][42][43] provided that sufficient CGM data were available both in terms of quantity (duration) and accuracy. 45,46 The sensitivity when using %TBR can be considerably greater than when using incidence of severe hypoglycemia because of the much higher frequency of observations and corresponding better accuracy measuring event rates.…”
Section: Resultsmentioning
confidence: 99%
“…1) and the corresponding regression analysis can be used to evaluate whether the relationships for two forms of therapy or other kinds of interventions are equivalent, corresponding to a single smooth relationship. 1,41,42,48,52 The graphical approach shown in Figure 1 has been used to examine the curvilinear relationships between incidence of severe hypoglycemia and HbA1c to compare the properties of three insulin formulations, viz., Neutral Protamine Hagedorn (NPH), glargine U-100, and detemir insulin. 41 Graphical analysis (cf.…”
Section: Two-dimensional Graphical Analyses Of Efficacy and Safetymentioning
confidence: 99%
“…Moreover, in Thomas Danne et al analysis, adding sotagliflozin to insulin therapy resulted in lower hypoglycemia events than the placebo group. Both 200 and 400mg of sotagliflozin were related to a substantially lower incidence of hypoglycemic attacks than placebo [17].…”
Section: Activity Of Sodium-glucose Co-transportermentioning
confidence: 85%